A Pedagogy of Provisioning: Urban Agriculture as a Mechanism for Community Renewal - Pam Karstens Ph.D. (Adult Education Research Conference, 2006)
This paper explores the significance of urban agriculture as a mechanism for teaching and learning to support the collective welfare of an inner-city neighborhood.